The Effect of Balancing Funds and Tobacco Excise Revenue Sharing Funds (DBH CHT) on Regional Expenditure Budget in West Nusa Tenggara Province - Aulia Manda, Sevtira; Wadi, Ikhwan (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2025)
The purpose of this study is to analyze the effect of balancing funds and tobacco excise revenue sharing funds (DBH CHT). The method in this study uses a quantitative research method. The sample of this study was 10 regencies/cities in West Nusa Tenggara, by analyzing the regional revenue and expenditure budget for the 2020-2024 period. The analysis in this study is Partial Least Square (PLS). The results of the study indicate that balancing funds have an influence and are significant to the regional government spending budget. tobacco excise revenue sharing funds (DBH CHT) do not have an influence and are significant to the regional government spending budget. The Balancing Fund and Tobacco Excise Revenue Sharing Fund (DBH CHT) play an important role in supporting the Regional Budget (APBD). The Balancing Fund aims to reduce the fiscal gap between the central and regional governments, while DBH CHT specifically assists regions in financing strategic sectors such as health, law enforcement, and public welfare, especially those related to the tobacco industry. The presence of these funds strengthens regional fiscal capacity, encourages equitable development, and improves the quality of public services at the regional level.